Leaf from Book 2 of On the fabric of the human body, verso - Vesalius, Andreas, 1514-1564. (Tufts University, Tisch Library, 2013)
Layout: Recto is printed in black ink of approximately 55 lines. Verso is notable for its detailed illustration of human dissection.; Originally printed in Basel by Joannes Oporinus, 1555. 1 leaf (printed on both sides) ; 40 cm.